Immunostimulanting effect of jackbean flour on non-specific immunity of mice in vitro and in silico - Riris Dewi Retnowati; Moh. Mirza Nuryady; Elly Purwanti; Sri Wahyuni; Iin Hindun (Green and Tropical Laboratory for Sustainability, 2024)
Background: Jackbean (Canavalia ensiformis) contains protein and secondary metabolite compounds, such as phenolics and flavonoids that can have potential as antioxidants, antibacterial, antimicrobial, and antiviral. Objectives: This study aims to determine the effect of giving jackbean flour as an immunostimulant on non-specific immunity of mice in-vitro and in-silico. Methods: This type of research is double methods research with a comparative method and uses an experimental design in the form of a Randomized Group Design and in-silico testing with the NCBI website. Mice with a total of 16 heads were divided into 4 treatment groups, namely the Negative Control group (P0), Dose 1 (P1) with a solution of jackbean flour as much as 2.3 g, Dose 2 (P2) as much as 4.6 g, Dose 3 (P3) as much as 9.2 g. The hemagglutination test was carried out on mice with a total of 16 mice. The hemagglutination test was carried out on the 15th day after giving the flour solution, then tested the content of active compounds in koro pedang in silico according to the literature review of previous research from the website which contains active compounds, namely canavanine, concanavalin A and B. Results: The results of in-vitro research show that the most influential dose for hemagglutination is P1 with a dose of 2.3 grams, characterized by almost all wells on the microplate there is concentrated clotting, and there is significance (p < 0.05) which means there is a difference in the effectiveness of jackbean flour solution as an immunostimulant from each dose. Conclusion: This study concluded that jack bean flour, especially at a dose of 2.3 grams, effectively enhanced non-specific immunity in mice, as evidenced by significant hemagglutination results. Therefore, jack bean flour has the potential to be a natural immunostimulant in improving immune health and fighting infections.